396 North American Multicenter Experience of the Flow-Redirection Endoluminal Device (FRED) in the Treatment of Intracranial Aneurysms. (April 2023) - Khorasanizadeh, MirHojjat; Shutran, Max; Schirmer, Clemens M.; Salem, Mohamed M.; Ringer, Andrew J.; Grandhi, Ramesh; Mitha, Alim P.; Levitt, Michael Robert; Jankowitz, Brian T.; Taussky, Phil; Thomas, Ajith J.; Moore, Justin M.; et al.
Abstract : INTRODUCTION: Flow-diverters have revolutionized the endovascular treatment of intracranial aneurysms. The evidence on the Flow Re-direction Endoluminal Device (FRED) is limited compared to some counterparts that have been available for clinical use longer. METHODS: Between June 2020 and November 2021, consecutive cerebral aneurysms treated using FRED were included across 7 North American centers. Data collected included patient demographics, aneurysm characteristics, peri-procedural and long-term complications, modified Rankin Scale (mRS) scores, and radiologic follow-up. RESULTS: 133 aneurysms in 116 patients treated in 123 FRED deployment procedures were included. One hundred twenty-six aneurysms (94.7%) were unruptured, 117 (88.0%) were saccular, and 123 (92.5%) aneurysms were located in the anterior circulation. Mean aneurysm maximal width and neck sizes were 7.2 mm and 4.1 mm, respectively. Successful FRED deployment was achieved in 122 (99.2%) procedures. Radiologic follow-up was available for 101 aneurysms at a median duration of 7.0 months. At the last follow-up, complete occlusion was observed in 55.4%, residual neck in 8.9%, and filling aneurysm in 35.6%. On multivariate regression analysis, age (OR = 0.93; p = 0.001) and aneurysm neck size (OR = 0.83; p = 0.048) negatively correlated with odds of complete occlusion. The retreatment rate was 6/124 (4.8%). The overall complication rate was 31/116 (26.7%). Parent vessel occlusion, covered branch occlusion, and in-stent stenosis were detected in 9/99 (9.1%), 6/63 (9.5%), and 15/99 (15.2%) of the cases, respectively. FRED-related, symptomatic, thromboembolic, and hemorrhagic complication rates were 22.4%, 12.9%, 6.9%, and 0.9% respectively. The morbidity rate was 10/116 (8.6%). CONCLUSIONS: As the first large-scale North American multi-center FRED experience, this study confirms FRED's ease of successful deployment but suggests a lower efficacy and higher rate of complications compared to previous European and South American FRED studies and other flow diverting devices.